2012
DOI: 10.1371/journal.pone.0038961
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Glucosamine Binding Leguminous Lectin with Mitogenic Activity towards Splenocytes and Anti-Proliferative Activity towards Tumor Cells

Abstract: A dimeric 64-kDa glucosamine-specific lectin was purified from seeds of Phaseolus vulgaris cv. “brown kidney bean.” The simple 2-step purification protocol involved affinity chromatography on Affi-gel blue gel and gel filtration by FPLC on Superdex 75. The lectin was absorbed on Affi-gel blue gel and desorbed using 1M NaCl in the starting buffer. Gel filtration on Superdex 75 yielded a major absorbance peak that gave a single 32-kDa band in SDS-PAGE. Hemagglutinating activity was completely preserved when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…Our results are in agreement with previous studies of Chan et al [47] that demonstrated the antiproliferative activity of some components of beans, different from phenolic compounds, on human breast cancer (MCF7), human hepatoma (Hep G2) and nasopharyngeal carcinoma (CNE1 and CNE2) cell line.…”
Section: Anti-cancer Activitysupporting
confidence: 94%
“…Our results are in agreement with previous studies of Chan et al [47] that demonstrated the antiproliferative activity of some components of beans, different from phenolic compounds, on human breast cancer (MCF7), human hepatoma (Hep G2) and nasopharyngeal carcinoma (CNE1 and CNE2) cell line.…”
Section: Anti-cancer Activitysupporting
confidence: 94%
“…Interestingly, O -glycan-binding lectins may also induce responses in lymphocytes [ 54 , 55 ]. The effect of lectins on adaptive immune cells is usually approached by analyzing the occurrence of lymphoproliferative responses [ 56 , 57 , 58 , 59 , 60 , 61 ], which we previously verified in ArtinM-stimulated murine spleen cells [ 24 ]. Isolated CD4 + and CD8 + T cells also proliferated under ArtinM stimulation in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 79%
“…Three-dimensional culture was first applied to PDT; we found that apoptosis of OS cells could be induced in 2D and 3D cell culture environments and that apoptosis is the main form of cell death by HMME-PDT. Formation of apoptotic bodies and chromatin condensation are remarkable features in apoptosis and can be visualized by the fluorescence of Hoechst 33342 lableing [20]. Chromatin condensation and nuclear pyknosis were observed with Hoechst 33342 in HMME-PDT groups.…”
Section: Discussionmentioning
confidence: 96%